Efflux pump regulatory genes mutations in multidrug resistance Pseudomonas aeruginosa isolated from wound infections in Isfahan hospitals - Vaez, Hamid (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Multidrug resistance Pseudomonas aeruginosa (MDR-P. aeruginosa) is a worldwide threat for public health. Hyperexpression of efflux pump systems (MexAB-OprM and MexCD-OprJ), which is a well-known mechanisms for MDR emerging, is controlled by regulatory genes, mexR and nfxB, respectively. The aim of this study was to evaluate point mutations in mexR and nfxB genes in MDR- P. aeruginosa isolated from wound infections. MATERIALS AND METHODS: A total of 34 P. aeruginosa cultures obtained from wound infections were analyzed. Among them eight isolates identified as MDR-P. aeruginosa and were subjected to determination of mutations in mexR and nfxB genes. RESULTS: We detected eight-point mutations in mexR and 12-point mutations in nfxB. The most common mutations were common G327-A (eight isolates), G384-A (eight isolates), G411-A (eight isolates). Mutations in A371-C and A372-C were the predominant substitution which was seen in nfxB. Amino acid substitutions were also found at position 124 and 126 for NfxB and MexR, respectively. CONCLUSIONS: P. aeruginosa isolates with mutation in efflux pump regulatory genes such as mexR and nfxB could be a main factor contributed to antibiotic resistance and must be considered in antibiotic treatment.